BIMBINGAN BELAJAR INTERAKTIF KOTA BANJARMASIN - Rafiqi, Fikri; Fawzia, Irma (UNIVERSITAS LAMBUNG MANGKURAT, 2024)
Most of the tutoring institutions in Banjarmasin City are less interactive and less interesting from an architectural perspective. This impacted on the decrease in atmosphere and quality of learning, as well as interest in learning. The atmosphere and quality of learning in tutoring institutions can be improved through architectural design with interactive design concepts and contemporary architectural method approaches. The interactive design concept focuses on the shape of the space and location of the tutoring to build a learning atmosphere that is interactive and psychologically interesting. The tutoring institution design uses contemporary architectural approach in order to optimize the interactive design concept.